High-temperature-resistant and high-modulus adhesive and preparation method thereof

By optimizing the monomer composition, crosslinking system, and preparation process of modified fillers, the problem of acrylate pressure-sensitive adhesives being unable to simultaneously achieve high temperature resistance and high modulus under high temperature conditions was solved, thus improving the mechanical stability and adhesive performance of the adhesives at high temperatures.

CN121673989APending Publication Date: 2026-03-17JIANGXI TA YI LAI POLYMER MATERIAL CO LTD

Patent Information

Application Number
CN202511786320.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-01
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing acrylic pressure-sensitive adhesives struggle to balance high temperature resistance, high modulus, and good adhesion performance in high-temperature environments. Furthermore, the poor compatibility between inorganic fillers and organic resin matrices leads to a decrease in bond strength and flexibility.

Method used

By rationally selecting monomer composition, crosslinking system, and modified filler, and optimizing preparation process parameters, a high-density and moderately tough crosslinked network is formed by using functional monomers composed of N-methoxymethylacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester, and a crosslinking agent composed of N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane, combined with modified nano-silica filler and segmented initiation polymerization process.

Benefits of technology

This technology enables adhesives to maintain excellent mechanical stability and high modulus at high temperatures, improves the interfacial compatibility between inorganic fillers and organic monomers, enhances bonding strength and thermal conductivity, and ensures the stability and consistency of product performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant and high-modulus adhesive and a preparation method thereof, and relates to the technical field of adhesives. The water-based adhesive comprises the following raw materials: 40-60 parts of a soft monomer, 20-30 parts of a hard monomer, 5-10 parts of a functional monomer, 1-3 parts of a cross-linking agent, 0.5-1.5 parts of an initiator, 2-5 parts of a modified nano filler and 30-50 parts of a solvent, the functional monomer is prepared by compounding N-methoxy methyl acrylamide, acrylic acid and 2-acrylic acid-hexahydro-4, 7-methylene-1H-indenyl ester according to a mass ratio of 2 to 1 to (1 to 1.5); the cross-linking agent is prepared by compounding N, N '-methylene bisacrylamide and 1, 1, 3, 3-tetramethyl-1, 3-divinyl disilazane according to a mass ratio of 1: (0.5 to 1). The adhesive has the advantages of favorable adhesive property, favorable high-temperature resistance and high modulus.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of adhesives, in particular to a high-temperature-resistant and high-modulus adhesive and a preparation method thereof. BACKGROUND

[0002] With the rapid development of electronic equipment, automobile industry and aerospace field, the demand for high-performance adhesives is increasing. High-temperature-resistant and high-modulus adhesives can maintain stable bonding performance and mechanical strength in high-temperature environments, and therefore have attracted widespread attention. Common pressure-sensitive adhesives on the market are mostly based on acrylate polymers, such as methyl acrylate, butyl acrylate and isooctyl acrylate. These materials usually have good initial adhesion and pressure-sensitive properties, but are prone to softening, creep or decomposition under long-term high-temperature conditions, resulting in bonding failure.

[0003] In order to improve the high-temperature resistance of acrylate pressure-sensitive adhesives, the existing technology often adopts the way of introducing monomers containing hydroxyl, carboxyl and other functional groups and crosslinking agents for crosslinking reaction, so as to enhance the high-temperature resistance by increasing the crosslinking density. However, this way often leads to a sharp increase in the modulus of the adhesive, a decrease in flexibility, and a serious impact on the initial adhesion and adhesion, making it difficult to balance the high-temperature resistance, high modulus and good bonding performance. In addition, some existing technologies add inorganic fillers (such as nano-silicon dioxide and aluminum oxide) to improve the modulus and high-temperature resistance of the adhesive, but the compatibility of inorganic fillers with organic resin matrix is poor, and agglomeration is easy to occur, which leads to a significant decrease in the bonding strength and flexibility of the adhesive, and also increases the difficulty and cost of preparing the adhesive.

[0004] To address the aforementioned problems, invention patent document CN116891707A discloses an acrylic pressure-sensitive adhesive, its preparation method, and its application. By weight, the raw material formulation of the high-temperature resistant pressure-sensitive adhesive includes 30-40 parts solvent, 25 parts (meth)acrylate monomer, 20-25 parts long-chain (meth)acrylate monomer, 10-15 parts double-bond organometallic chelating agent, 5-10 parts double-bond silane coupling agent, 5-10 parts high-temperature resistant additives, 0.5-5.5 parts thermal initiator, 0.5-1.5 parts crosslinking agent, 0.5-1.5 parts antioxidant, and 0.5-1.5 parts polymerization inhibitor. The high-temperature resistant thermosetting acrylic adhesive of this invention has a solid content of 60-70%, and the resulting product exhibits high-temperature resistance ≥100℃, moderate mechanical properties, and good stability at high temperatures. It can be used to form a rapidly adhering pressure-sensitive tape by coating with a mold before curing and can be used as a protective film pressure-sensitive adhesive. However, this invention introduces a large number of special components such as double-bonded organometallic chelating agents and double-bonded silane coupling agents to improve high-temperature resistance, which not only significantly increases the cost of raw materials and the complexity of the preparation process, but also leads to a significant decrease in the initial tack and holding power of the adhesive. At the same time, a single crosslinking agent system cannot achieve a balance between high modulus and flexibility.

[0005] Therefore, developing an acrylic pressure-sensitive adhesive that can meet the requirements of high temperature resistance and high modulus, while ensuring good initial tack, holding power and peel strength, has become an urgent technical problem to be solved in this field. Summary of the Invention

[0006] The main objective of this invention is to overcome the above-mentioned shortcomings and provide a high-temperature resistant and high-modulus adhesive and its preparation method. By rationally selecting monomer composition, crosslinking system and modified filler, and optimizing preparation process parameters, the high-temperature resistance, modulus and bonding performance of the adhesive are synergistically improved.

[0007] To achieve the above objectives, the present invention provides a high-temperature resistant and high-modulus adhesive, which, by mass parts, comprises: 40-60 parts of soft monomer, 20-30 parts of hard monomer, 5-10 parts of functional monomer, 1-3 parts of crosslinking agent, 0.5-1.5 parts of initiator, 2-5 parts of modified nanofiller, and 30-50 parts of solvent; wherein the functional monomer is N-methoxymethylacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a mass ratio of 2:1:(1-1.5); and the crosslinking agent is N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane in a mass ratio of 1:(0.5-1).

[0008] Preferably, the soft monomer is at least one of butyl acrylate and isooctyl acrylate.

[0009] Preferably, the hard monomer is at least one selected from methyl acrylate, methyl methacrylate, styrene, and acrylonitrile.

[0010] Preferably, the initiator is azobisisobutyronitrile.

[0011] Preferably, the preparation method of the modified nanofiller includes the following steps: adding nano-silica to an ethanol aqueous solution and ultrasonically dispersing for 20-30 min; then adding silane coupling agent KH-570 and stirring the reaction at 68-72℃ for 2-3 h; after the reaction is completed, centrifuging to separate the precipitate, vacuum drying the precipitate at 80-90℃ for 4-6 h, and grinding it to obtain the modified nanofiller.

[0012] Preferably, the average particle size of the nano-silica is 10-80 nm.

[0013] Preferably, the volume ratio of ethanol to water in the ethanol-water solution is (3-5):1.

[0014] Preferably, the mass ratio of the nano-silica, the aqueous ethanol solution, and the silane coupling agent KH-570 is 1:10:(0.05-0.08).

[0015] Preferably, the solvent is a mixture of ethyl acetate and toluene in a mass ratio of (2-3):1.

[0016] Another object of the present invention is to provide a method for preparing the aforementioned high-temperature resistant and high-modulus adhesive, comprising the following steps: Step S1: Weigh the soft monomer, hard monomer, and functional monomer according to the mass fractions, mix them evenly to obtain a mixed monomer; add it to a reaction vessel equipped with a stirrer and a thermometer, then add 50% of the solvent and all the modified nanofillers according to the formula; first stir at high speed of 300-400 r / min for 15-20 min to initially mix the materials; then use an ultrasonic disperser with a power of 400-600W to ultrasonically disperse for 20-25 min to form a uniform and stable dispersion system; Step S2: Heat the jacket of the reactor to raise the temperature of the dispersion system to 70-75℃; weigh 30% of the initiator according to the formula, dissolve it in a solvent to prepare an initiator solution with a mass percentage concentration of 15-25%; slowly add the initiator solution dropwise to the dispersion system, controlling the dropwise addition time to 15-20 min; after the dropwise addition is completed, maintain the temperature at 70-75℃ and react at a stirring speed of 150-200 r / min for 1-1.5 h; Step S3: Mix the remaining solvent and the remaining initiator evenly to obtain the initiator replenishment solution; while maintaining the reactor temperature at 75-80℃, slowly add the initiator replenishment solution dropwise into the reactor, controlling the dropwise addition time to 3-4 hours; during the dropwise addition process, maintain the stirring speed at 200-250 r / min, and take samples every 30 minutes to detect the solid content of the system to ensure that the solid content steadily increases; Step S4: Raise the temperature of the reactor to 85-90℃ and continue to keep it at that temperature for 2-2.5 hours; then lower the temperature of the system to 60-65℃, add the crosslinking agent of the formula, stir at 250-300 r / min for 10 minutes to disperse the crosslinking agent evenly, then reduce the temperature to 150-200 r / min and stir for 1-1.5 hours to form a stable crosslinking network and obtain the adhesive base material; Step S5: Cool the adhesive base material to below 40℃, add 0.1-0.3% of antioxidant 1010 by weight of the total base material, and stir for 30 minutes for stabilization treatment; then filter with a 1000-mesh filter cloth; coat the filtered base material evenly onto the PET substrate using a coating machine, with the coating thickness controlled at 20-30μm; send the coated substrate into the drying tunnel for gradient drying to complete curing; finally, cool to room temperature by cooling rollers and roll up to obtain a high-temperature resistant and high-modulus adhesive product.

[0017] Preferably, in step S5, the temperature of the first drying tunnel is 60-70℃ and the drying time is 5-8 min; the temperature of the second drying tunnel is 90-100℃ and the drying time is 8-10 min; and the temperature of the third drying tunnel is 110-120℃ and the drying time is 5-6 min.

[0018] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The high-temperature resistant and high-modulus adhesive disclosed in this invention achieves a rigid and flexible molecular chain structure by precisely controlling the ratio range of soft monomers, hard monomers, and functional monomers, and by using a functional monomer system composed of N-methoxymethacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a specific mass ratio, combined with a crosslinking agent composed of N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane. After the crosslinking reaction, this structure forms a high-density and moderately tough crosslinked network, effectively solving the technical bottleneck of traditional adhesives that are difficult to balance high temperature resistance and high modulus, enabling the product to maintain excellent mechanical stability under high temperature conditions.

[0019] (2) The high-temperature resistant and high-modulus adhesive disclosed in this invention is composed of N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane in a mass ratio of 1:(0.5-1). By introducing N,N'-methylenebisacrylamide, a dense chemical cross-linking network can be formed in the pressure-sensitive adhesive system. The cross-linking structure can firmly bind the molecular chains, greatly reducing the displacement and deformation of the molecular chains at high temperatures. This can significantly improve the modulus of the pressure-sensitive adhesive and enhance its high-temperature resistance, avoiding delamination and residue problems in high-temperature environments. The silicon-nitrogen bond introduced by 1,1,3,3-tetramethyl-1,3-divinyldisilazane has a higher bond energy than the silicon-oxygen bond, resulting in superior thermal stability. Furthermore, the polarity of the nitrogen atom enhances intermolecular forces and inhibits high-temperature chain relaxation. It can copolymerize with the double bonds of the acrylate backbone to form a stable hybrid structure, significantly improving modulus and high-temperature creep resistance, and also enhancing the weather resistance of the adhesive layer, making it suitable for extreme high-temperature applications such as aerospace. The combined effect of these two components results in adhesives with superior high-temperature resistance and higher modulus.

[0020] (3) The high-temperature resistant and high-modulus adhesive disclosed in this invention is composed of N-methoxymethylacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a mass ratio of 2:1:(1-1.5). 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester introduces an indenyl structure, which is rigid and has a compact spatial structure. After being incorporated into the main chain, it can significantly restrict the rotation and relaxation of the molecular chain, thereby increasing the glass transition temperature and modulus. It has excellent thermal stability, avoiding softening and deformation of the adhesive layer at high temperatures. The N-methoxymethylacrylamide molecule contains both acrylamide groups and methoxy active groups, which can effectively enhance the rigidity of the molecular chain and improve the interfacial adhesion. Acrylic acid improves the polymerization conversion rate by regulating the reactivity of the system through the carboxyl group, and at the same time, it improves the compatibility by utilizing the interaction between the carboxyl group and the hydroxyl group on the filler surface. The three work together to ensure that the adhesive has both high modulus and high-temperature resistance.

[0021] (4) The high-temperature resistant and high-modulus adhesive disclosed in this invention introduces nano-silica modified with silane coupling agent KH-570 as a filler. By optimizing the modification process parameters (ultrasonic dispersion time, reaction temperature and time, drying conditions, etc.) and raw material ratio (mass ratio of nano-silica, ethanol aqueous solution and silane coupling agent), the interfacial compatibility between the nano-filler and the organic monomer matrix is ​​significantly improved. The modified nano-filler is uniformly dispersed in the system to form rigid support points, which work synergistically with the crosslinking network. This not only greatly improves the modulus of the adhesive, but also enhances the thermal conductivity, significantly reducing the deformation rate of the product at high temperatures. This overcomes the technical problem of performance fluctuation caused by the easy agglomeration of unmodified nano-fillers.

[0022] (5) The high-temperature resistant and high-modulus adhesive disclosed in this invention adopts a staged initiation polymerization and gradient heating reaction preparation process. By controlling the amount of initiator, dropping rate, stirring speed and reaction temperature at different stages, the monomer polymerization process is precisely controlled. The combination of high-speed stirring and ultrasonic dispersion in the early stage ensures the uniform dispersion of modified nanofillers. The staged addition of initiator and solvent in the middle stage ensures the stable progress of the polymerization reaction and guarantees a steady increase in solid content. The high-temperature insulation and stepwise addition of crosslinking agent in the later stage promote the full formation of crosslinking network. This process effectively avoids the problem of uneven molecular chain distribution caused by concentrated exothermic reaction in traditional polymerization processes, and improves the stability and batch consistency of product performance.

[0023] (6) The high-temperature resistant and high-modulus adhesive disclosed in this invention further enhances the overall performance of the adhesive by optimizing the solvent compounding system (ethyl acetate and toluene compounded in a specific ratio), the gradient drying process in the curing stage (three-stage drying tunnels with different temperatures and times), and the subsequent addition of antioxidants and fine filtration. The solvent system ensures good solubility and dispersibility of monomers and fillers, gradient drying achieves efficient solvent removal and stable curing of the crosslinking network, and the addition of antioxidants enhances the anti-aging performance of the product. The final product forms a uniform adhesive layer on the PET substrate with strong adhesion, exhibiting excellent bonding strength and modulus stability in high-temperature environments, and has a wider range of applications. Detailed Implementation

[0024] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art. Example 1

[0025] A high-temperature resistant and high-modulus adhesive, by mass parts, comprises: 40 parts soft monomer, 20 parts hard monomer, 5 parts functional monomer, 1 part crosslinking agent, 0.5 parts initiator, 2 parts modified nanofiller, and 30 parts solvent; wherein the functional monomer is N-methoxymethylacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a mass ratio of 2:1:1; and the crosslinking agent is N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane in a mass ratio of 1:0.5.

[0026] The soft monomer is butyl acrylate; the hard monomer is methyl acrylate; the initiator is azobisisobutyronitrile; and the solvent is a mixture of ethyl acetate and toluene in a mass ratio of 2:1.

[0027] The preparation method of the modified nanofiller includes the following steps: adding nano-silica to an ethanol aqueous solution and ultrasonically dispersing for 20 min; then adding silane coupling agent KH-570 and stirring at 68℃ for 2 h; after the reaction is completed, centrifuging to separate the precipitate, vacuum drying at 80℃ for 4 h, and grinding to obtain the modified nanofiller; the average particle size of the nano-silica is 10 nm; the volume ratio of ethanol to water in the ethanol aqueous solution is 3:1; the mass ratio of nano-silica, ethanol aqueous solution, and silane coupling agent KH-570 is 1:10:0.05.

[0028] A method for preparing the aforementioned high-temperature resistant and high-modulus adhesive includes the following steps: Step S1: Weigh the soft monomer, hard monomer, and functional monomer according to the mass fractions and mix them evenly to obtain a mixed monomer; add it to a reaction vessel equipped with a stirrer and a thermometer, then add 50% of the solvent and all the modified nanofillers according to the formula; first stir at a high speed of 300 r / min for 15 min to make the materials initially mixed; then use an ultrasonic disperser with a power of 400W to ultrasonically disperse for 20 min to form a uniform and stable dispersion system; Step S2: Heat the jacket of the reactor to raise the temperature of the dispersion system to 70°C; weigh 30% of the initiator according to the formula and dissolve it in a solvent to prepare an initiator solution with a mass percentage concentration of 15%; slowly add the initiator solution dropwise to the dispersion system, controlling the dropwise addition time to 15 min; after the dropwise addition is completed, maintain the temperature at 70°C and react at a stirring speed of 150 r / min for 1 h; Step S3: Mix the remaining solvent and the remaining initiator evenly to obtain the initiator replenishment solution; while maintaining the reactor temperature at 75℃, slowly add the initiator replenishment solution dropwise into the reactor, controlling the dropwise addition time to 3 hours; during the dropwise addition process, maintain the stirring speed at 200 r / min, and take samples every 30 minutes to detect the solid content of the system to ensure that the solid content steadily increases; Step S4: Raise the temperature of the reactor to 85°C and continue to keep it at that temperature for 2 hours; then lower the temperature of the system to 60°C, add the crosslinking agent of the formula, stir at 250 r / min for 10 minutes to disperse the crosslinking agent evenly, then reduce the temperature to 150 r / min and stir for 1 hour to form a stable crosslinking network and obtain the adhesive base material. Step S5: Cool the adhesive base material to below 40℃, add 0.1% of antioxidant 1010 by weight of the total base material, and stir for 30 minutes for stabilization treatment; then filter using a 1000-mesh filter cloth; uniformly coat the filtered base material onto the PET substrate using a coating machine, controlling the coating thickness to 20μm; sequentially feed the coated substrate into the drying tunnels for gradient drying to complete curing; finally, cool to room temperature using cooling rollers and roll up to obtain a high-temperature resistant and high-modulus adhesive product; the gradient drying in step S5 is as follows: the first drying tunnel temperature is 60℃, drying time is 5 minutes; the second drying tunnel temperature is 90℃, drying time is 8 minutes; the third drying tunnel temperature is 110℃, drying time is 5 minutes. Example 2

[0029] A high-temperature resistant and high-modulus adhesive, by mass parts, comprises: 45 parts soft monomer, 23 parts hard monomer, 6 parts functional monomer, 1.5 parts crosslinking agent, 0.7 parts initiator, 3 parts modified nanofiller, and 35 parts solvent; wherein the functional monomer is N-methoxymethylacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a mass ratio of 2:1:1.2; and the crosslinking agent is N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane in a mass ratio of 1:0.6.

[0030] The soft monomer is isooctyl acrylate; the hard monomer is methyl methacrylate; the initiator is azobisisobutyronitrile; and the solvent is a mixture of ethyl acetate and toluene in a mass ratio of 2.3:1.

[0031] The preparation method of the modified nanofiller includes the following steps: adding nano-silica to an ethanol aqueous solution and ultrasonically dispersing for 23 min; then adding silane coupling agent KH-570 and stirring at 69℃ for 2.3 h; after the reaction is completed, centrifuging to separate the precipitate, vacuum drying at 83℃ for 4.5 h, and grinding to obtain the modified nanofiller; the average particle size of the nano-silica is 30 nm; the volume ratio of ethanol to water in the ethanol aqueous solution is 3.5:1; the mass ratio of nano-silica, ethanol aqueous solution, and silane coupling agent KH-570 is 1:10:0.06.

[0032] A method for preparing the aforementioned high-temperature resistant and high-modulus adhesive includes the following steps: Step S1: Weigh the soft monomer, hard monomer, and functional monomer according to the mass fractions, mix them evenly to obtain a mixed monomer; add it to a reaction vessel equipped with a stirrer and a thermometer, then add 50% of the solvent and all the modified nanofillers according to the formula; first stir at high speed of 330 r / min for 17 min to make the materials initially mixed; then use an ultrasonic disperser with a power of 450W to ultrasonically disperse for 22 min to form a uniform and stable dispersion system; Step S2: Heat the jacket of the reactor to raise the temperature of the dispersion system to 72°C; weigh 30% of the initiator according to the formula and dissolve it in a solvent to prepare an initiator solution with a mass percentage concentration of 17%; slowly add the initiator solution dropwise to the dispersion system, controlling the dropwise addition time to 17 min; after the dropwise addition is completed, maintain the temperature at 72°C and react at a stirring speed of 160 r / min for 1.2 h; Step S3: Mix the remaining solvent and the remaining initiator evenly to obtain the initiator replenishment solution; while maintaining the reactor temperature at 77°C, slowly add the initiator replenishment solution dropwise into the reactor, controlling the dropwise addition time at 3.3 h; during the dropwise addition process, maintain the stirring speed at 220 r / min, and take samples every 30 min to detect the solid content of the system to ensure that the solid content steadily increases; Step S4: Raise the temperature of the reactor to 87°C and continue to keep it at that temperature for 2.2 hours. Then lower the temperature of the system to 62°C, add the crosslinking agent according to the formula, stir at 260 r / min for 10 minutes to disperse the crosslinking agent evenly, and then reduce the temperature to 160 r / min and stir for 1.2 hours to form a stable crosslinking network and obtain the adhesive base material. Step S5: Cool the adhesive base material to below 40℃, add 0.15% of antioxidant 1010 by weight of the total base material, and stir for 30 minutes for stabilization treatment; then filter using a 1000-mesh filter cloth; uniformly coat the filtered base material onto the PET substrate using a coating machine, controlling the coating thickness to 23μm; sequentially feed the coated substrate into the drying tunnels for gradient drying to complete curing; finally, cool to room temperature using cooling rollers and roll up to obtain a high-temperature resistant and high-modulus adhesive product; the temperature of the first drying tunnel in step S5 is 63℃, and the drying time is 6 minutes; the temperature of the second drying tunnel is 93℃, and the drying time is 8.5 minutes; the temperature of the third drying tunnel is 112℃, and the drying time is 5.2 minutes. Example 3

[0033] A high-temperature resistant and high-modulus adhesive, by mass parts, comprises: 50 parts soft monomer, 25 parts hard monomer, 7.5 parts functional monomer, 2 parts crosslinking agent, 1 part initiator, 3.5 parts modified nanofiller, and 40 parts solvent; wherein the functional monomer is N-methoxymethylacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a mass ratio of 2:1:1.3; and the crosslinking agent is N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane in a mass ratio of 1:0.75.

[0034] The soft monomer is butyl acrylate; the hard monomer is styrene; the initiator is azobisisobutyronitrile; and the solvent is a mixture of ethyl acetate and toluene in a mass ratio of 2.5:1.

[0035] The preparation method of the modified nanofiller includes the following steps: adding nano-silica to an ethanol aqueous solution and ultrasonically dispersing for 25 min; then adding silane coupling agent KH-570 and stirring at 70 °C for 2.5 h; after the reaction is completed, centrifuging to separate the precipitate, vacuum drying at 85 °C for 5 h, and grinding to obtain the modified nanofiller; the average particle size of the nano-silica is 50 nm; the volume ratio of ethanol to water in the ethanol aqueous solution is 4:1; the mass ratio of nano-silica, ethanol aqueous solution, and silane coupling agent KH-570 is 1:10:0.065.

[0036] A method for preparing the aforementioned high-temperature resistant and high-modulus adhesive includes the following steps: Step S1: Weigh the soft monomer, hard monomer, and functional monomer according to the mass fractions, mix them evenly to obtain a mixed monomer; add it to a reaction vessel equipped with a stirrer and a thermometer, then add 50% of the solvent and all the modified nanofillers according to the formula; first stir at high speed of 350 r / min for 18 min to make the materials initially mixed; then use an ultrasonic disperser with a power of 500W to ultrasonically disperse for 23 min to form a uniform and stable dispersion system. Step S2: Heat the jacket of the reactor to raise the temperature of the dispersion system to 73°C; weigh 30% of the initiator according to the formula and dissolve it in a solvent to prepare an initiator solution with a mass percentage concentration of 20%; slowly add the initiator solution dropwise to the dispersion system, controlling the dropwise addition time to 18 min; after the dropwise addition is completed, maintain the temperature at 73°C and react at a stirring speed of 180 r / min for 1.3 h; Step S3: Mix the remaining solvent and the remaining initiator evenly to obtain the initiator replenishment solution; while maintaining the reactor temperature at 78°C, slowly add the initiator replenishment solution dropwise into the reactor, controlling the dropwise addition time at 3.5h; during the dropwise addition, maintain the stirring speed at 230r / min, and take samples every 30min to detect the solid content of the system to ensure that the solid content steadily increases; Step S4: Raise the temperature of the reactor to 88°C and continue to keep it at that temperature for 2.3 hours. Then lower the temperature of the system to 63°C, add the crosslinking agent according to the formula, stir at 280 r / min for 10 minutes to disperse the crosslinking agent evenly, and then reduce the temperature to 180 r / min and stir for 1.3 hours to form a stable crosslinking network and obtain the adhesive base material. Step S5: Cool the adhesive base material to below 40℃, add 0.2% of antioxidant 1010 by weight of the total base material, and stir for 30 minutes for stabilization treatment; then filter using a 1000-mesh filter cloth; uniformly coat the filtered base material onto the PET substrate using a coating machine, controlling the coating thickness to 25μm; sequentially feed the coated substrate into the drying tunnels for gradient drying to complete curing; finally, cool to room temperature using cooling rollers and roll up to obtain a high-temperature resistant and high-modulus adhesive product; the temperature of the first drying tunnel in step S5 is 65℃, and the drying time is 6.5 minutes; the temperature of the second drying tunnel is 95℃, and the drying time is 9 minutes; the temperature of the third drying tunnel is 115℃, and the drying time is 5.5 minutes. Example 4

[0037] A high-temperature resistant and high-modulus adhesive, by mass parts, comprises: 55 parts soft monomer, 28 parts hard monomer, 9 parts functional monomer, 2.5 parts crosslinking agent, 1.3 parts initiator, 4.5 parts modified nanofiller, and 45 parts solvent; wherein the functional monomer is N-methoxymethacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a mass ratio of 2:1:1.4; and the crosslinking agent is N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane in a mass ratio of 1:0.9.

[0038] The soft monomer is a mixture of butyl acrylate and isooctyl acrylate in a mass ratio of 3:5; the hard monomer is a mixture of methyl acrylate, methyl methacrylate, styrene, and acrylonitrile in a mass ratio of 1:1:2:1; the initiator is azobisisobutyronitrile; and the solvent is a mixture of ethyl acetate and toluene in a mass ratio of 2.8:1.

[0039] The preparation method of the modified nanofiller includes the following steps: adding nano-silica to an ethanol aqueous solution and ultrasonically dispersing for 28 min; then adding silane coupling agent KH-570 and stirring at 71 °C for 2.8 h; after the reaction is completed, centrifuging to separate the precipitate, vacuum drying at 88 °C for 5.5 h, and grinding to obtain the modified nanofiller; the average particle size of the nano-silica is 70 nm; the volume ratio of ethanol to water in the ethanol aqueous solution is 4.5:1; the mass ratio of nano-silica, ethanol aqueous solution, and silane coupling agent KH-570 is 1:10:0.075.

[0040] A method for preparing the aforementioned high-temperature resistant and high-modulus adhesive includes the following steps: Step S1: Weigh the soft monomer, hard monomer, and functional monomer according to the mass fractions, mix them evenly to obtain a mixed monomer; add it to a reaction vessel equipped with a stirrer and a thermometer, then add 50% of the solvent and all the modified nanofillers according to the formula; first stir at high speed of 390 r / min for 19 min to make the materials initially mixed; then use an ultrasonic disperser with a power of 550W to ultrasonically disperse for 24 min to form a uniform and stable dispersion system. Step S2: Heat the jacket of the reactor to raise the temperature of the dispersion system to 74°C; weigh 30% of the initiator according to the formula and dissolve it in a solvent to prepare an initiator solution with a mass percentage concentration of 23%; slowly add the initiator solution dropwise to the dispersion system, controlling the dropwise addition time to 19 min; after the dropwise addition is completed, maintain the temperature at 74°C and react at a stirring speed of 190 r / min for 1.4 h; Step S3: Mix the remaining solvent and the remaining initiator evenly to obtain the initiator replenishment solution; while maintaining the reactor temperature at 79°C, slowly add the initiator replenishment solution dropwise into the reactor, controlling the dropwise addition time at 3.8h; during the dropwise addition process, maintain the stirring speed at 240r / min, and take samples every 30min to detect the solid content of the system to ensure that the solid content steadily increases; Step S4: Raise the temperature of the reactor to 89°C and continue to keep it at that temperature for 2.4 hours; then lower the temperature of the system to 64°C, add the crosslinking agent of the formula, stir at 290 r / min for 10 minutes to disperse the crosslinking agent evenly, then reduce the temperature to 190 r / min and stir for 1.4 hours to form a stable crosslinking network and obtain the adhesive base material; Step S5: Cool the adhesive base material to below 40℃, add 0.25% of antioxidant 1010 by weight of the total base material, and stir for 30 minutes for stabilization treatment; then filter using a 1000-mesh filter cloth; uniformly coat the filtered base material onto the PET substrate using a coating machine, controlling the coating thickness to 28μm; sequentially feed the coated substrate into the drying tunnels for gradient drying to complete curing; finally, cool to room temperature using cooling rollers and roll up to obtain a high-temperature resistant and high-modulus adhesive product; the temperature of the first drying tunnel in step S5 is 68℃, and the drying time is 7.5 minutes; the temperature of the second drying tunnel is 98℃, and the drying time is 9.5 minutes; the temperature of the third drying tunnel is 118℃, and the drying time is 5.8 minutes. Example 5

[0041] A high-temperature resistant and high-modulus adhesive, by mass parts, comprises: 60 parts soft monomer, 30 parts hard monomer, 10 parts functional monomer, 3 parts crosslinking agent, 1.5 parts initiator, 5 parts modified nanofiller, and 50 parts solvent; wherein the functional monomer is N-methoxymethylacrylamide, acrylic acid, and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester in a mass ratio of 2:1:1.5; and the crosslinking agent is N,N'-methylenebisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyldisilazane in a mass ratio of 1:1.

[0042] The soft monomer is butyl acrylate; the hard monomer is acrylonitrile; the initiator is azobisisobutyronitrile; and the solvent is a mixture of ethyl acetate and toluene in a mass ratio of 3:1.

[0043] The preparation method of the modified nanofiller includes the following steps: adding nano-silica to an ethanol aqueous solution and ultrasonically dispersing for 30 min; then adding silane coupling agent KH-570 and stirring at 72℃ for 3 h; after the reaction is completed, centrifuging to separate the precipitate, vacuum drying at 90℃ for 6 h, and grinding to obtain the modified nanofiller; the average particle size of the nano-silica is 80 nm; the volume ratio of ethanol to water in the ethanol aqueous solution is 5:1; the mass ratio of nano-silica, ethanol aqueous solution, and silane coupling agent KH-570 is 1:10:0.08.

[0044] A method for preparing the aforementioned high-temperature resistant and high-modulus adhesive includes the following steps: Step S1: Weigh the soft monomer, hard monomer, and functional monomer according to the mass fractions, mix them evenly to obtain a mixed monomer; add it to a reaction vessel equipped with a stirrer and a thermometer, then add 50% of the solvent and all the modified nanofillers according to the formula; first stir at high speed of 400 r / min for 20 min to make the materials initially mixed; then use an ultrasonic disperser with a power of 600W to ultrasonically disperse for 25 min to form a uniform and stable dispersion system; Step S2: Heat the jacket of the reactor to raise the temperature of the dispersion system to 75°C; weigh 30% of the initiator according to the formula and dissolve it in a solvent to prepare an initiator solution with a mass percentage concentration of 25%; slowly add the initiator solution dropwise to the dispersion system, controlling the dropwise addition time to 20 min; after the dropwise addition is completed, maintain the temperature at 75°C and react at a stirring speed of 200 r / min for 1.5 h; Step S3: Mix the remaining solvent and the remaining initiator evenly to obtain the initiator replenishment solution; while maintaining the reactor temperature at 80℃, slowly add the initiator replenishment solution dropwise into the reactor, controlling the dropwise addition time to 4 hours; during the dropwise addition process, maintain the stirring speed at 250 r / min, and take samples every 30 minutes to detect the solid content of the system to ensure that the solid content steadily increases; Step S4: Raise the temperature of the reactor to 90°C and continue to keep it at that temperature for 2.5 hours. Then lower the temperature of the system to 65°C, add the crosslinking agent according to the formula, stir at 300 r / min for 10 minutes to disperse the crosslinking agent evenly, and then reduce the temperature to 200 r / min and stir for 1.5 hours to form a stable crosslinking network and obtain the adhesive base material. Step S5: Cool the adhesive base material to below 40℃, add 0.3% of antioxidant 1010 by weight of the total base material, and stir for 30 minutes for stabilization treatment; then filter using a 1000-mesh filter cloth; uniformly coat the filtered base material onto the PET substrate using a coating machine, controlling the coating thickness to 30μm; sequentially feed the coated substrate into the drying tunnels for gradient drying to complete curing; finally, cool to room temperature using cooling rollers and roll up to obtain a high-temperature resistant and high-modulus adhesive product; the gradient drying in step S5 is as follows: the first drying tunnel temperature is 70℃, drying time is 8 minutes; the second drying tunnel temperature is 100℃, drying time is 10 minutes; the third drying tunnel temperature is 120℃, drying time is 6 minutes.

[0045] Comparative Example 1 A high-temperature resistant and high-modulus adhesive and its preparation method are basically the same as those in Example 1, except that an equal amount of N-methoxymethacrylamide is used instead of hexahydro-4,7-methylene-1H-indenyl ester.

[0046] Comparative Example 2 A high-temperature resistant and high-modulus adhesive and its preparation method are basically the same as those in Example 1, except that an equal amount of hexahydro-4,7-methylene-1H-indenyl ester is used instead of N-methoxymethylacrylamide.

[0047] Comparative Example 3 A high-temperature resistant and high-modulus adhesive and its preparation method are basically the same as those in Example 1, except that an equal amount of N,N'-methylenebisacrylamide is used instead of 1,1,3,3-tetramethyl-1,3-divinyldisilazane.

[0048] Comparative Example 4 A high-temperature resistant and high-modulus adhesive and its preparation method are basically the same as those in Example 1, except that an equal amount of 1,1,3,3-tetramethyl-1,3-divinyldisilazane is used instead of N,N'-methylenebisacrylamide.

[0049] To further illustrate the beneficial technical effects of the high-temperature resistant and high-modulus adhesives involved in the various embodiments of the present invention, relevant performance tests were conducted on the high-temperature resistant and high-modulus adhesives involved in Example 1 and Comparative Examples 1-4. The test results are shown in Table 1, and the test methods are as follows: (1) Tensile shear strength: The tensile shear strength test was carried out in accordance with GB / T 7124-2008 "Determination of tensile shear strength of adhesives (rigid material to rigid material)"; the tensile speed was 5 mm / min, and the test temperature was room temperature and 200℃.

[0050] (2) Energy storage modulus at 25℃: tested using a TA rheometer at a frequency of 1Hz.

[0051] Table 1. Test results of high temperature resistant and high modulus adhesive properties Item Tensile Shear Strength Tensile Shear Strength at 200°C Storage Modulus at 25°C Unit MPa MPa KPa Example 1 21.5 21.3 4600 Comparative Example 1 18.0 12.5 3200 Comparative Example 2 16.5 14.3 3800 Comparative Example 3 19.3 15.0 3500 Comparative Example 4 17.0 16.3 4100 As can be seen from Table 1, the high-temperature resistant and high-modulus adhesive of Example 1 has significantly better overall performance than the comparative example. The combined use of N-methoxymethacrylamide, hexahydro-4,7-methylene-1H-indenyl ester, 1,1,3,3-tetramethyl-1,3-divinyldisilazane and N,N'-methylenebisacrylamide is beneficial to improving the above performance.

[0052] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention. The scope of protection claimed by the appended claims and their equivalents is defined.

Claims

1. A high temperature resistant and high modulus adhesive, characterized by, The raw material composition includes, in mass fraction, 40-60 parts of soft monomer, 20-30 parts of hard monomer, 5-10 parts of functional monomer, 1-3 parts of crosslinking agent, 0.5-1.5 parts of initiator, 2-5 parts of modified nano filler, and 30-50 parts of solvent; the functional monomer is a compound of N-methoxy methacrylamide, acrylic acid and 2-acrylic acid-hexahydro-4,7-methylene-1H-indenyl ester at a mass ratio of 2:1:(1-1.5); and the crosslinking agent is a compound of N,N'-methylene bisacrylamide and 1,1,3,3-tetramethyl-1,3-divinyl disilazane at a mass ratio of 1:(0.5-1).

2. The high temperature and high modulus resistant adhesive according to claim 1, wherein, The soft monomer is at least one of butyl acrylate and isooctyl acrylate.

3. The high temperature and high modulus resistant adhesive according to claim 1, wherein, The hard monomer is at least one of methyl acrylate, methyl methacrylate, styrene and acrylonitrile.

4. The high temperature and high modulus resistant adhesive according to claim 1, wherein, The initiator is azobisisobutyronitrile.

5. The high temperature and high modulus resistant adhesive according to claim 1, wherein, The preparation method of the modified nano filler includes the following steps: adding nano silicon dioxide into an ethanol aqueous solution, ultrasonic dispersion for 20-30 min; then adding silane coupling agent KH-570, stirring and reacting at 68-72 ℃ for 2-3 h; after the reaction, centrifugal separation is performed, the precipitate is vacuum dried at 80-90 ℃ for 4-6 h, and the modified nano filler is obtained after grinding.

6. The high temperature and high modulus resistant adhesive according to claim 5, wherein, The average particle size of the nano silicon dioxide is 10-80 nm; and the volume ratio of ethanol to water in the ethanol aqueous solution is (3-5):

1.

7. The high temperature and high modulus resistant adhesive according to claim 5, wherein, The mass ratio of the nano silicon dioxide, the ethanol aqueous solution and the silane coupling agent KH-570 is 1:10:(0.05-0.08).

8. The high temperature and high modulus resistant adhesive of claim 1, wherein, The solvent is a compound of ethyl acetate and toluene at a mass ratio of (2-3):

1.

9. A process for the preparation of the high temperature resistant and high modulus adhesive according to any one of claims 1 to 8, characterized in that, The method includes the following steps: Step S1: the soft monomer, the hard monomer and the functional monomer are weighed in mass fraction, uniformly mixed to obtain a mixed monomer, added into a reaction kettle provided with a stirring paddle and a thermometer, 50% of the solvent and all the modified nano filler are added, high-speed stirring is performed at 300-400 r / min for 15-20 min to preliminarily mix the materials, and an ultrasonic disperser with a power of 400-600 W is used for ultrasonic dispersion for 20-25 min to form a uniform and stable dispersion system; Step S2: the jacket of the reaction kettle is heated to raise the temperature of the dispersion system to 70-75 ℃, 30% of the initiator in the formula is weighed, dissolved with the solvent to prepare an initiator solution with a mass percentage concentration of 15-25%, the initiator solution is slowly added into the dispersion system, the dropping time is controlled to be 15-20 min, after the dropping is completed, the temperature is kept at 70-75 ℃, and the reaction is performed at a stirring speed of 150-200 r / min for 1-1.5 h; Step S3: the remaining solvent and the remaining initiator are uniformly mixed to obtain an initiator supplement solution, the initiator supplement solution is slowly added into the reaction kettle under the condition that the temperature of the reaction kettle is kept at 75-80 ℃, the dropping time is controlled to be 3-4 h, the stirring speed is kept at 200-250 r / min during the dropping process, and the solid content of the system is detected every 30 min to ensure that the solid content is steadily increased; Step S4: the temperature of the reactor is raised to 85-90°C, and the reaction is continued for 2-2.5 h; then the temperature of the system is lowered to 60-65°C, and the crosslinking agent is added in the amount specified in the formula, first stirred at 250-300 r / min for 10 min to uniformly disperse the crosslinking agent, then stirred at 150-200 r / min for 1-1.5 h to form a stable crosslinking network, and a glue base is obtained; Step S5: the glue base is cooled to below 40°C, 0.1-0.3% of the total mass of the base of antioxidant 1010 is added, and the mixture is stirred for 30 min for stabilization treatment; then the mixture is filtered using 1000-mesh filter cloth; the filtered base is uniformly coated on a PET substrate using a coating machine, and the coating thickness is controlled to be 20-30 μm; the coated substrate is sequentially sent into the drying tunnel for gradient drying to complete curing; finally, the substrate is cooled to room temperature by a cooling roller, and a high-temperature-resistant and high-modulus adhesive product is obtained.

10. The method for preparing the high-temperature resistant and high-modulus adhesive according to claim 9, characterized in that, The first drying tunnel in step S5 has a temperature of 60-70°C, and a drying time of 5-8 min; the second drying tunnel has a temperature of 90-100°C, and a drying time of 8-10 min; and the third drying tunnel has a temperature of 110-120°C, and a drying time of 5-6 min.

Citation Information

Patent Citations

  • Acrylate pressure-sensitive adhesive as well as preparation method and application thereof

    CN116891707A

Cited By

  • Non-uv wafer bg thinning adhesive tape and preparation method thereof

    CN122146179A